Factors associated with women's desire for control of healthcare during childbirth: Psychometric analysis and construct validation. Issue 4 (23rd April 2019) - Stevens, Natalie R.; Adams, Natasia; Wallston, Kenneth A.; Hamilton, Nancy A.
Abstract: The desire for control of healthcare is a significant moderator of outcomes related to childbirth. Researchers have shown that a sense of control of healthcare during childbirth is strongly correlated with postpartum maternal well‐being. The aims of this study were to examine (a) the psychometric characteristics of an instrument to assess women's desire for control of healthcare during childbirth, and (b) examine desire for control in relation to parity, medical complications of pregnancy, and women's choices of childbirth providers and setting. The study design was cross‐sectional using two different samples totaling 385 pregnant women. In Sample 1, ( n  = 193) we conducted an exploratory factor analysis to reduce the initial item pool. In Sample 2, ( n  = 192) we conducted a confirmatory factor analysis (CFA) of the final 12‐item instrument and examined factors related to the desire for control. Results of the analysis in Sample 1 were supportive of a single‐factor structure reflecting women's desire to influence the childbirth healthcare environment and decision‐making. The final 12‐item instrument had high internal consistency reliability (Cronbach's alpha = 0.93). CFA in Sample 2 was supportive of the single‐factor structure with good model fit. The desire for control was directly correlated with an internal locus of control. Nulliparous women reported a lower desire for control compared with multiparous women. The desire for control among women with self‐reported medical complications of pregnancy was comparable to that among women without pregnancy complications. The desire for control was a predictor of choosing midwives (vs. obstetricians), home or birth center (vs. hospitals), and professional labor support (e.g., doulas). Implications for future research on the impact of desire for control on maternal health outcomes are discussed.